DNA Ligase IV Prevents Replication Fork Stalling and Promotes Cellular Proliferation in Triple Negative Breast Cancer. (31st January 2019) - Joshi, Rashmi R.; Ali, Sk Imran; Ashley, Amanda K.
Abstract : DNA damage is a hallmark of cancer, and mutation and misregulation of proteins that maintain genomic fidelity are associated with the development of multiple cancers. DNA double strand breaks are arguably considered the most deleterious type of DNA damage. The nonhomologous end-joining (NHEJ) pathway is one mechanism to repair DNA double strand breaks, and proteins involved in NHEJ may also regulate DNA replication. We previously established that DNA-PKcs, a NHEJ protein, promotes genomic stability and cell viability following cellular exposure to replication stress; we wanted to discern whether another NHEJ protein, DNA ligase IV (Lig4), shares this phenotype. Our investigations focused on triple negative breast cancer cells, as, compared to nonbasal breast cancer, LIG4 is frequently amplified, and an increased gene dose is associated with higher Lig4 expression. We depleted Lig4 using siRNA and confirmed our knockdown by qPCR and western blotting. Cell survival diminished with Lig4 depletion alone, and this was associated with increased replication fork stalling. Checkpoint protein Chk1 activation and dephosphorylation were unchanged in Lig4-depleted cells. Lig4 depletion resulted in sustained DNA-PKcs phosphorylation following hydroxyurea exposure. Understanding the effect of Lig4 on genomic replication and the replication stress response will clarify the biological ramifications of inhibiting Lig4 activity. In addition, Lig4 is an attractive clinical target for directing CRISPR/Cas9-mediated repair towards homology-directed repair and away from NHEJ, thus understanding of how diminishing Lig4 impacts cell biology is critical.